A SPEECH ACT ANALYSIS OF DIRECT UTTERANCES ON SHORT STORY THE ENCHANCTED FISH - Lasma Dwina (Universitas Lampung, 2015)
Direct utterance is usually used in daily conversation. This research is aimed at (1) identifying the mode of the direct sentences on short story entitled the Enchanted Fish, (2) describing the purposes of the direct utterances in short story entitled the Enchanted Fish. The object used to be analyzed are direct utterances of short story the Enchanted Fish. In collecting the data, the writer uses observation method by selecting the direct utterances which can be found. Having analyzed the data, the writer found that (1) the mode of direct sentences are divided into three; declarative sentence, interrogative sentences and imperative sentences; (2) related to the purpose of utterances, the writer finds that the purposes of utterances depends on the locution, illocution, and perlocution. Related to maxims, the writer found that there is violation on relevance based on unequal status of interlocutors (3). Different culture has different perceptions and interpretations of appropriateness and politeness.Key words: direct utterance, locution, illocution, perlocution